MENUMBUHKEMBANGKAN KETERAMPILAN MENULIS ANAK SEKOLAH DASAR - Prayitno Prayitno (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2014)
Approach or conventional writing instructional strategies used by teachers in teaching in primary schools is not a product-oriented writing process so that it is necessary to develop the skills of how to write a children's elementary school. One way in developing writing skills, using the approach Writers Workshop. Teaching procedures using Writers Workshop approach is implemented through: (1) teaching mini, 5-15 minutes, (2) write freely, for 30-45 minutes, and discussion (sharing) for 10-15 minutes with classmates. Therefore develop writing skills Elementary School children will effectively be done with one approach Writers Workshop. Keywords: skills of children, writing skill